TF Profiler: a transcription factor inference method that broadly measures transcription factor activity and identifies mechanistically distinct networks - Taylor Jones; Rutendo F. Sigauke; Lynn Sanford; Dylan J. Taatjes; Mary A. Allen; Robin D. Dowell (Genome Biology)
Abstract TF Profiler is a method of inferring transcription factor (TF) regulatory activity, i.e., when a TF is present and actively participating in the regulation of transcription, directly from nascent sequencing assays such as PRO-seq and GRO-seq. While ChIP assays have measured DNA localization, they fall short of identifying when and where the effector domain of a transcription factor is active. Our method uses RNA polymerase activity to infer TF effector domain activity across hundreds of data sets and transcription factors. TF Profiler is broadly applicable, providing regulatory insights on any PRO-seq sample for any transcription factor with a known binding motif.